Toroidal plasma acceleration due to NBI fast ion losses in LTX-β. (5th July 2021) - Hughes, P E; Capecchi, W; Elliott, D B; Zakharov, L E; Bell, R E; Hansen, C; Boyle, D P; Gorelenkov, S N; Majeski, R; Kaita, R
Abstract: The recent Lithium Tokamak Experiment-Beta (LTX- β ) upgrade includes the addition of neutral beam injection (NBI) in the same direction as the plasma current (co- I P ) and a new toroidal Mirnov array for MHD characterization. In initial NBI experiments, a spontaneously rotating n = 1 MHD mode is seen to accelerate during NBI in the counter-beam direction, accompanied by a rise in electron density consistent with the beam-injected inventory but without a clear increase in plasma pressure. Together with analytic and numerical modeling of beam optics and fast ion confinement, these observations indicate the prompt loss of all or nearly all beam ions. However, the same modeling also suggests that planned upgrades to the Ohmic heating system should provide the fast ion confinement necessary for beam heating and core fueling. A simple analytic model relates the momentum confinement time τ ϕ to the observed evolution of mode rotation due to the combination of NBI momentum coupling, fast ion loss J ⃗ × B ⃗, and anomalous viscous torques, yielding τ ϕ values consistent with past measurements of electron energy confinement time τ E, e .